The DC-factory : energy efficient, robust, forward-looking - Sauer, Alexander (Hanser Publishers, 2021)
"The energy revolution has many facets. One of them is the power supply of factories. Here lies the origin of the upheaval in drive technology, which today is already based on direct current, while the grid supplies alternating current. In this book you will learn the advantages of building a comprehensive direct current factory network into which all power generators feed their energy and from which all consumers are supplied directly.All related conceptual, economic, technical and organizational issues are dealt within this book:- Potential and economic assessment of the direct current factory in comparison with a current factory supplied with alternating current- System concept draft for the necessary system and device adjustments with concrete solutions for implementation- Detailed treatment of all relevant technical topics, such as topology, voltage level, supply concepts, grounding and network types, EMC, pre-charging- Characteristic-based control of a direct current network with different supply devices and loads- Guarantee of network stability, even with highly dynamic loads and without additional communication- Treatment of essential security aspects- Planning and design of a direct current network in your own factory, including presentation of the planning tasks and instructions for the user. The book also shows four real applications that were implemented with the manufacturer-independent direct current network described. Different conceptual focal points are explained in each case in order to demonstrate the possible range of use."--Page 4 of cover.